2020
DOI: 10.3390/ijms21124393
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Peripheral Arterial Disease (PAD): A Review on Oxidative Disorders

Abstract: Peripheral arterial disease (PAD) is an atherosclerotic disease that affects a wide range of the world’s population, reaching up to 200 million individuals worldwide. PAD particularly affects elderly individuals (>65 years old). PAD is often underdiagnosed or underestimated, although specificity in diagnosis is shown by an ankle/brachial approach, and the high cardiovascular event risk that affected the PAD patients. A number of pathophysiologic pathways operate in chronic arterial ischemia of lower limbs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 104 publications
0
32
0
5
Order By: Relevance
“…The pathophysiology of atherosclerotic plaque involves complex interactions between cholesterol metabolism and vascular cell activity. It is also known that disturbance of the laminar arterial flow in PAD plays an essential role in the adhesion of inflammatory blood cells to the arterial wall and plays a role in plaque generation [ 14 ]. The hemodynamic consequences of atherosclerotic plaque depend on the degree of stenosis/occlusion.…”
Section: Molecular Basis Of Vessel Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology of atherosclerotic plaque involves complex interactions between cholesterol metabolism and vascular cell activity. It is also known that disturbance of the laminar arterial flow in PAD plays an essential role in the adhesion of inflammatory blood cells to the arterial wall and plays a role in plaque generation [ 14 ]. The hemodynamic consequences of atherosclerotic plaque depend on the degree of stenosis/occlusion.…”
Section: Molecular Basis Of Vessel Diseasementioning
confidence: 99%
“…A narrowed vessel progresses towards chronic total occlusion. LEAD patients demonstrate high grades of inflammation and active oxidative stress, which are vital mechanisms in PAD pathophysiology [ 14 ]. There is an interest in the vaso-protective effects of heme oxygenase 1 (HO-1) as a potential antioxidant by affecting the proliferation, migration, and adhesion of smooth vascular muscle cells, endothelial cells, and leukocytes [ 15 ].…”
Section: Molecular Basis Of Vessel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Functional capacity is reduced in chronic peripheral arterial occlusive disease (PAOD) because of the atherosclerotic process involving the peripheral arteries, 1 with consequent obstruction of the blood flow to the lower limbs, provoking the classic symptom known as intermittent claudication. 2 The shorter the distance an individual can walk before claudication sets in, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In 30 RCTs, including 1816 patients with IC, pain-free walking distance and MWD increased on average 82 and 109 meters, respectively, in up to two years. [4][5][6][7][8][9] A meta-analysis of 25 randomized studies (1,054 patients) addressing exercise strategies in the rehabilitation of patients with PAD, found that supervised treadmill exercise was better than the control group, with a gain of 128 meters in pain-free walking distance and 180 meters at the maximum walking distance. In contrast, 3 RCTs (n=493) with PAD found that home walking exercises, when combined with behavior change techniques, improved the 6-minute walking test distance more than interventions on a supervised treadmill (45-54 meters vs. 33-35 meters, respectively).…”
mentioning
confidence: 99%